"We Count What Matters": Students' Color-Blind "Merit-Based" Logic and the Reproduction of Inequality in a College Admissions Activity. Issue 3 (July 2019) - Matthew, Ervin (Maliq); Gast, Melanie Jones; Broscoe, Molly
The authors introduce a college admissions simulation activity that facilitates discussions of affirmative action and racial disparities in the seemingly objective college admissions process. In this activity, students serve as mock admissions committees in small groups. On the basis of activity sheets collected from multiple courses across several institutions, the authors disclose quantitative patterns in students' applicant choices and qualitative themes reflecting students' decision making processes. The authors discuss how this activity and subsequent class discussion help students to recognize and think through meritocratic assumptions and color-blind practices that reproduce racial inequality.